Research status of cutting machining NiTi shape memory alloys: a comprehensive review - Junying Wei; Lei Yang; Guijie Wang; Chengming Gong; Feiyang Yang (Frontiers in Materials)
NiTi shape memory alloys (SMA) have garnered significant interest owing to their shape memory effect, superior corosion resistance, and biocompatibility. This paper reviewed the current research status of cutting machining for NiTi SMA, focusing on turning, milling, and drilling processes, emphasizing the influence of various cutting parameters, tool materials, and cooling methods on machining performance. The optimal turning effect under dry cutting circumstances is achieved when the cutting speed surpasses 100 m/min. The application of Minimum Quantity Lubrication (MQL) in milling, alongside the use of cold air and the optimization of parameters such as feed rate and cutting depth, could diminish cutting force and temperature, thus reducing burr formation. Cemented carbide and high-speed steel covered with TiN are the ideal materials for drilling tools, and the use of substantial cutting fluid yields superior cutting performance compared to MQL. This review concludes that, despite advancements in the study of machining NiTi shape memory alloys, further research is necessary to enhance the efficiency and quality of NiTi SMA machining, particularly with tool material selection and cooling techniques. Finally, based on the current research results, this paper proposes possible future research directions, which provides valuable theoretical guidance for the processing research of NiTi SMA.